Influence of two nitrification inhibitors (DCD and DMPP) on annual ryegrass yield and soil mineral N dynamics after incorporation with cattle slurry - Fangueiro, D. (2015)
Nitrogen (N) losses through nitrate leaching, occurring after slurry spreading, can be reduced by the use of nitrification inhibitors (NIs) such as dicyandiamide (DCD) and 3,4-dimethyl pyrazole phosphate (DMPP). In the present work, the effects of DCD and DMPP, applied at two rates with cattle slurry, on soil mineral N profiles, annual ryegrass yield, and N uptake were compared under similar pedoclimatic conditions. Both NIs delayed the nitrate formation in soil; however, DMPP ensured that the soil mineral N was predominantly in the ammonium form rather than in the nitrate form for about 100 days, whereas with DCD such effect was observed only during the first 40 days after sowing. Furthermore, the use of NIs led to an increase of the drymatter (DM) yields in a range of 32–54% and of the forage N removal in a range of 34–68% relative to the slurry-only (SO) treatment (without NIs). A DM yield of 8698 kg ha21 was obtained with the DMPP applied at the greater rate against only 7444 kg ha21 obtained with the greater rate of DCD (4767 kg ha21 in the SO treatment). Therefore, it can be concluded that DMPP is more efficient as an NI than DCD when combined with cattle slurry